Convenient synthesis of (2R)- and (2S)-2-(1-methylethyl)-5-oxo-2-phenylpentanenitrile, intermediates in the preparation of phenylalkylamine calcium channel blockers - Gilmore, Jeremy; Prowse, Will; Steggles, David; Urquhart, Michael; Olkowski, Jennifer (Journal of the Chemical Society, Perkin Transactions 1, 1996)
The multigram synthesis of (2S)- and (2R)-2-(1-methylethyl)-5-oxo-2-phenylpentanenitriles 9a and 9b is described, using either (4R)-2,2-dimethyl-1,3-dioxolan-4-ylmethanol or (2R)-butane-1,2,4-triol as chiral auxiliary, The configuration of an intermediate dioxolane 10b is assigned by X-ray crystallography. The synthetic utility of the aldehydes is demonstrated by conversion to both enantiomers of the calcium antagonist noremopamil in >98% enantiomeric excess (ee). The enantiomeric purity of the final amines is assayed by H-1 NMR spectroscopy in the presence of the chiral solvating agent (1R)-(-)-2,2,-trifluoro-1-(9-anthryl)ethanol.